Reconfigurable Dual-Band Microstrip Antenna for Middle Band 5G Applications - Abbas Mahmoud, Zahra; Khalid Jassim, Ali; Hadi Wali, Musa (Iraqi Journal for Electrical and Electronic Engineering, 2026)
A reconfigurable inset-fed Microstrip Patch Antenna (MPA) for dual-band behavior and stable-radiation direction hasbeen demonstrated in this research. The suggested reconfigurable antenna has dimensions of 60×50 mm2 and is printedon an FR4 substrate that is 1.5 mm thick and has a dielectric constant (εr) and loss tangent (tanδ) equal to 4.3 and 0.02,respectively. An inset-fed line with an impedance of 50Ω is used to feed the proposed antenna structure. The parasiticcapacitance is efficiently added to the proposed structure by using the slitline approach. The proposed antenna is testedand simulated, where the result shows two resonant frequencies with S11 values less than -10 dB (S11 ≤ −10). The firstresonant frequency is found at 2.45 GHz with a value equal to -30.5 dB, while the second resonant is found at 3.54 GHzwith a value equal to -32 dB. Moreover, the slits include two PIN diodes. After analyzing the antenna, two reconfigurablebands are obtained for various uses with stable radiation direction. The suggested antenna is constructed and measured,and the outputs of the simulation and the measurements show good agreement.